EFEKTIVITAS PEMBELAJARAN SEJARAH BERBASIS PROYEK DENGAN MEDIA SCRAPBOOK UNTUK MENINGKATKAN KREATIVITAS MAHASISWA - Junita Yosephine Sinurat; Andre Mustofa Meihan (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2026)
This research aims to measure the effectiveness of project-based history learning using scrapbook media in increasing student creativity. The research subjects were 28 3rd semester students in class R001 of the History Education Study Program, Jambi University. The method used is pre-experimental design with a one-group pretest-posttest design model, through three stages: pretest, learning implementation, and post-test. The pretest aims to measure students' initial creative abilities using a questionnaire with a Likert scale (1-5). The average pretest score was 69.89. Furthermore, project-based learning was implemented using the Project-Based Learning (PjBL) model with scrapbook media in the Indonesian History of the Age of Western Influence course. Learning stages include project planning, monitoring, assessment, and reflection. After implementation, a post-test was carried out to measure changes in creativity. The average post-test score increased to 108.68, indicating a significant increase. The results of statistical tests via paired sample t-test showed a significant value (0.000 < 0.05), which indicates a significant difference between the pretest and post-test results . Thus, project-based history learning using scrapbook media has proven to be effective in increasing student creativity.